Bridging Youth to Global Education: Workshop on IELTS Awareness and Preparation at SMAN Jatinangor: Bridging Youth to Global Education: Workshop on IELTS Awareness and Preparation at SMAN Jatinangor - Revi Nur Ridwan (Institut Riset dan Publikasi Indonesia, 2025)
Many high school students in suburban areas lack awareness of international English proficiency tests like IELTS, limiting their access to global education opportunities. To address this, a one-day interactive workshop was held at SMAN Jatinangor using the Participatory Learning and Action (PLA) approach. The program introduced students to IELTS structure, objectives, and test strategies through engaging, student-centered activities. Pre- and post-surveys assessed the impact, with results showing a significant improvement: the percentage of students in the high awareness category increased from 0% to 70%, while the low category was completely eliminated. This demonstrates the effectiveness of targeted educational interventions in bridging global readiness gaps.